Transforming Civil Procedural Law in the Digital Era: Evidence, Contracts, and Legal Certainty - Siregar, Dahris (Universitas Semarang, 2025)
This study examines the transformation of Indonesian civil procedural law in responding to the growing use of electronic contracts and digital evidence in the era of electronic commerce. Although electronic contracts have been formally recognized under Law Number 11 of 2008 on Electronic Information and Transactions and its amendment, Law Number 19 of 2016, their application in civil dispute resolution continues to raise legal uncertainty, particularly in relation to evidentiary standards. This research employs a normative juridical method using statutory, conceptual, and analytical approaches to analyze the conformity of electronic contracts with the requirements of contract validity under Article 1320 of the Civil Code and their position within the evidentiary system governed by Article 1866 of the Civil Code. The findings demonstrate that electronic contracts possess evidentiary value equivalent to written documents, provided that electronic information and documents are accessible, readable, verifiable, and their authenticity and integrity are ensured through lawful electronic systems, digital signatures, and digital forensic verification. Furthermore, electronic evidence is affirmed as an extension of written evidence within civil procedural law, thereby strengthening legal certainty in civil disputes arising from digital transactions. The novelty of this research lies in its confirmation that the theory of civil procedural evidence accommodates electronic contracts as legally valid proof comparable to conventional written evidence, as long as both formal and substantive legal requirements are fulfilled. Accordingly, this study underscores the urgency of harmonizing civil procedural law with technological developments to enhance legal certainty, evidentiary reliability, and justice in Indonesia’s digital transaction framework.